2018
DOI: 10.2147/ppa.s156552
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting vulnerable patients’ preferences regarding colorectal cancer screening: a systematic review

Abstract: BackgroundPatient preferences are important to consider in the decision-making process for colorectal cancer (CRC) screening. Vulnerable populations, such as racial/ethnic minorities and low-income, veteran, and rural populations, exhibit lower screening uptake. This systematic review summarizes the existing literature on vulnerable patient populations’ preferences regarding CRC screening.MethodsWe searched the CINAHL, PsycINFO, PubMed, Scopus, and Web of Science databases for articles published between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Several studies found that in making CRC screening decisions most individuals prefer to consult their physician [52][53][54]. This might be especially the case for vulnerable patients such as racial/ethnic minorities and lowincome individuals as these groups exhibit lower screening uptake [55]. This shared decision making should not only focus on the colonoscopy as a yes or no option, but should also function as a counselling opportunity to offer participants emotional support and strategies for coping with the positive FIT in case of not (yet) undergoing the colonoscopy.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Several studies found that in making CRC screening decisions most individuals prefer to consult their physician [52][53][54]. This might be especially the case for vulnerable patients such as racial/ethnic minorities and lowincome individuals as these groups exhibit lower screening uptake [55]. This shared decision making should not only focus on the colonoscopy as a yes or no option, but should also function as a counselling opportunity to offer participants emotional support and strategies for coping with the positive FIT in case of not (yet) undergoing the colonoscopy.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…For these reasons, fecal testing is a preferred testing modality by many low-income individuals. [9][10][11] Consequently, programs to increase CRC screening in low-income populations have leveraged the relatively simple and low-cost fecal test to encourage participation. 9,12,13 Multiple studies have demonstrated the effectiveness of such strategies, including mailing reminders and mailing fecal immunochemical test (FIT) kits to age-eligible individuals who are not up to date with screening.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure uptake of recommendations, the choice of screening strategy should depend on the individual's preferences, test availability, and the strategy that the patient is most likely to complete and adhere to [1,6,9]. The existing literature on preferences for screening strategies shows high variability in preferences across studies [10][11][12][13] and, since guidelines have previously recommended screening at age 50, few studies have included younger people or explicitly tested differences in preferences by age.…”
Section: Preferences For Screening Strategiesmentioning
confidence: 99%